2021
DOI: 10.21931/rb/2021.01.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the micropropagation of elite adult trees of Sequoia sempervirens: forest species of interest in the Basque Country, Spain

Abstract: Forest trees are renewable sources of timber and other valuable non-timber products. Nowadays, the increase in population and demand for forestry products results in overexploitation of forestry. Therefore, there is an urgent need to produce elite plants with higher productivity under stress derived from climate change to have available to afforestation. For this reason, propagation methods should be improved to be more efficient in terms of quality and productivity. The main species planted in the Basque Coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 45 publications
3
4
1
Order By: Relevance
“…The highest NS/E was obtained in BT explants cultured in QL medium (Experiment 1). In accordance with this result, in previous experiments in our lab, the highest number of NS/E was obtained in S. sempervirens when explants bigger than 1.5 cm in length were used [10]. Similarly, Hine et al [29] and Rafi and Salehi [44] developed an in vitro protocol for C. japonica and Cedrus deodara, using explants of mature trees from 1.0 to 2.5 cm in length, respectively.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The highest NS/E was obtained in BT explants cultured in QL medium (Experiment 1). In accordance with this result, in previous experiments in our lab, the highest number of NS/E was obtained in S. sempervirens when explants bigger than 1.5 cm in length were used [10]. Similarly, Hine et al [29] and Rafi and Salehi [44] developed an in vitro protocol for C. japonica and Cedrus deodara, using explants of mature trees from 1.0 to 2.5 cm in length, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…During Experiment 2, explants cultured with BA or m-T showed an efficient organogenic response regarding shoot induction percentage, and although not significant, a slightly higher response in BT explants induced with BA was observed. Analogous results were obtained in several organogenesis protocols from adult trees of Pinus pinea, P. radiata, Sequoia sempervirens, and P. halepensis, where, to obtain an in vitro shoot response, BA at concentrations ranging from 4.4 to 50 µM was utilized [10,[40][41][42][43].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In the same way, in P. sylvestris and P. pinaster , a higher rate of organogenic response was obtained by using m-T instead of BA [ 36 , 46 ]. However, in other studies of our group, no improvement was found when using m-T instead of BA for the induction of axillary shoots in P. radiata and Sequoia sempervirens [ 20 , 32 , 41 ]. Summarizing, the effect of different cytokinins at different concentrations depends on the species and the initial explant used to initiate the in vitro culture.…”
Section: Discussionmentioning
confidence: 71%
“…As has been recently reviewed, factors such as explant source and plant growth regulators influence the in vitro regeneration of plants via organogenesis in different species [ 30 , 31 , 32 ]. In this regard, other authors mentioned that cotyledon explants had several advantages over embryonic explants [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%